The Relationship between Family Support and Emotional Mental Disorders in Adolescents - Devita, Yeni; Okviani, Nadia; Emulyani, Emulyani; Erlin, Fitry (Universitas Prima Indonesia, 2025)
Adolescent emotional disorders are behaviors that are not in accordance with their age stages. The number of problems and deviant behaviors in adolescence shows that adolescents are a risk group for emotional mental disorders. The purpose of the study was to determine the relationship between family social support and emotional mental disorders in adolescents. This type of quantitative research has a cross-sectional design. The research sample is 288 respondents. The sampling technique uses stratified random sampling. Data collection was carried out using a social support questionnaire and a Strenght and Difficulties Questionnaire (SDQ) questionnaire. The data was analyzed by the Chi square test. The results of the univariate analysis related to the characteristics of the respondents were almost all (94.8%) of the respondents were at the age of 12-15 years (early adolescence) as many as 273 people, and more than half (68.1%) of the respondents were female as many as 196 people. In terms of the frequency distribution of family support, half of the respondents did not get family support as many as 146 respondents (50.7%). Frequency distribution of the frequency of adolescent emotional mental disorders almost half of the respondents had emotional disorders in the borderline range as many as 123 respondents (42.7%). The results of the statistical test obtained p-value = 0.00 < 0.05 so that it can be concluded that there is a relationship between family support and adolescent mental disorders. There needs to be high family social support to prevent mental disorders in adolescents.